APLIKASI CALON PERSEORANGAN SEBAGAI KEPALA DAERAH DALAM PENYELENGGARAAN PEMERINTAHAN DI DAERAH - Retno Saraswati (Masalah-Masalah Hukum, 2010)
Candidate of Chief of Local Government in local election is not can only nominated by political party or alliance of political parties, but it can nominated by individual. The masterpiece of chief of local government as a transformative leader is synchronization of local government system based on political system and presidential of democracy, according to commendation of UUD 1945. The worried that existence of individual candidate susceptible peeps out problems for stabilization of presidential government-system because that it doesn't get political support from Local Parliament simply unprovable in Garut district. Political relation between Chief of Local Government and Local Parliament as element of local government-management based on the relation of parallelism and partnership in the effort to get public prosperous.